2010
DOI: 10.1007/s10228-010-0155-5
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive activity in the checkered snapper, Lutjanus decussatus, off Ishigaki Island, Okinawa

Abstract: The checkered snapper, Lutjanus decussatus, is an important species for fisheries in the Okinawan region. This study estimated the reproduction of this lutjanid species in the waters around Ishigaki Island. The main spawning season was estimated to be between June and October, since oocytes at the maturation stage and/or postovulatory follicles were found during the study period. In the main spawning season, high gonadosomatic index values were found around the time of the last quarter moon for each month from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…From the WoS and OBIS analyses of sub-regions and taxa occurrences it became clear, as in many other marine regions (Hughes, Bellwood & Connolly, 2002), that serious taxonomic and geographic biases are present in marine research in the RYS. Some of this taxonomic bias may stem from the commercial importance of Pisces and Crustacea in Japan, which has resulted in many studies on various species’ lifecycles and aquaculture methodologies (e.g., Hamasaki & Kitada, 2008; Nanami et al, 2010). Research on these topics, while often conducted somewhere in the RYS, generally did not include field observations or sampling information as the focus was more on ex situ analyses and model species.…”
Section: Discussionmentioning
confidence: 99%
“…From the WoS and OBIS analyses of sub-regions and taxa occurrences it became clear, as in many other marine regions (Hughes, Bellwood & Connolly, 2002), that serious taxonomic and geographic biases are present in marine research in the RYS. Some of this taxonomic bias may stem from the commercial importance of Pisces and Crustacea in Japan, which has resulted in many studies on various species’ lifecycles and aquaculture methodologies (e.g., Hamasaki & Kitada, 2008; Nanami et al, 2010). Research on these topics, while often conducted somewhere in the RYS, generally did not include field observations or sampling information as the focus was more on ex situ analyses and model species.…”
Section: Discussionmentioning
confidence: 99%
“…Most coral reef fish spawn according to the lunar cycle (Johannes, 1978;Doherty, 1983;Takemura et al, 2004 a;Takemura et al, 2004 b;Nanami et al 2010). The spawn ing pattern of this species has previously been reported in a few coral reef fish, such as butterfly fish (Ralston, 1981).…”
Section: Discussionmentioning
confidence: 95%
“…During non-spawning seasons (between November 2020 and April 2021, and between November and December 2021), underwater observations were conducted around two lunar phases (last-quarter moon and new moon). This was because: (1) preliminary surveys between September and October 2020 revealed the fish aggregations of the two snapper species were found around the last-quarter moon and new moon and (2) Nanami et al (2010) showed that Lutjanus decussatus showed a greater peak of ovary development during the last-quarter moon.…”
Section: Methodsmentioning
confidence: 99%
“…Two snapper species, checkered snapper Lutjanus decussatus (Cuvier, 1828) and blackspot snapper L. fulviflamma (Forsskål, 1775), are important fisheries target species in Okinawan coral reefs ( Akita et al, 2016 ). Nanami et al (2010) indicated the possibility that L. decussatus forms spawning aggregations in this region by clarifying its reproductive biology. The main spawning season was between June and October and clear lunar-synchronized fluctuations in the gonadsomatic index (GSI) of females were found.…”
Section: Introductionmentioning
confidence: 99%